2023
DOI: 10.1097/md.0000000000032986
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric myelin oligodendrocyte glycoprotein antibody associated disease—Asymmetric papilledema and elevated ICP are two of the chameleons: A case report

Abstract: Background: Myelin oligodendrocyte glycoprotein antibody (MOGA) associated diseases are inflammatory immune-mediated demyelinating disorders with relapse potential involving the central nervous system. Multiple unusual clinical manifestations of those disorders were reported, making treatment decisions difficult.Case presentation: A healthy 12-year-old obese boy presented with headache and bilateral asymmetric papilledema. The patient had a negative medical history. His neurological and general examinations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Extensive research has demonstrated that individuals maintaining MOG-IgG seropositivity throughout followup are at a higher likelihood of experiencing recurrence; hence, emphasizing the importance of early diagnosis, meticulous follow-up, and precise prognostic assessments. 8 The MOG protein's form and glycosylation are crucial for anti-MOG antibody recognition. 2 In a retrospective analysis involving 135 individuals with acute optic neuritis (ON), Hickman et al identified nine cases where aberrant MRI enhancement occurred in the intracranial optic nerve just anterior to the optic chiasm.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research has demonstrated that individuals maintaining MOG-IgG seropositivity throughout followup are at a higher likelihood of experiencing recurrence; hence, emphasizing the importance of early diagnosis, meticulous follow-up, and precise prognostic assessments. 8 The MOG protein's form and glycosylation are crucial for anti-MOG antibody recognition. 2 In a retrospective analysis involving 135 individuals with acute optic neuritis (ON), Hickman et al identified nine cases where aberrant MRI enhancement occurred in the intracranial optic nerve just anterior to the optic chiasm.…”
Section: Case Reportmentioning
confidence: 99%
“…Investigating potential associations between MOGA-related diseases and elevated ICP is imperative for comprehensive clinical assessment. 8 The current absence of randomized controlled studies for MOGAD necessitates reliance on empirical treatment recommendations, often drawn from prior research. Highdose steroids, in line with their common use in other acquired inflammatory demyelinating diseases, serve as the primary first-line treatment for MOGA-related disorders.…”
Section: Case Reportmentioning
confidence: 99%
“…Over time, the presence of myelin oligodendrocyte glycoprotein (MOG)-autoantibodies in serum has grown to include various unique presentations, ranging from optic neuritis to encephalomyelitis [1]. The most common clinical manifestation of MOGAD is MOGAD-associated encephalitis, with optic neuritis being the second [2]. Of note, optic neuritis in MOGAD differs from MS as it tends to be bilateral and leads to severe visual deficits if left untreated [2].…”
Section: Introductionmentioning
confidence: 99%
“…The most common clinical manifestation of MOGAD is MOGAD-associated encephalitis, with optic neuritis being the second [2]. Of note, optic neuritis in MOGAD differs from MS as it tends to be bilateral and leads to severe visual deficits if left untreated [2].…”
Section: Introductionmentioning
confidence: 99%